Tren Penggunaan Kecerdasan Buatan (AI) dalam Meningkatkan Pembelajaran Mahasiswa: Kajian Literatur - Yollanda, Febri; Ramona (Asosiasi Dosen Akuntansi Indonesia, 2024)
This article examines the trend of using artificial intelligence (AI) to enhance student learning and the opportunities and challenges that arise in the digital era. A literature review was conducted using the PRISMA method to identify and analyze related studies. The results show that AI has great potential in personalizing learning, increasing access to learning materials, and providing real-time feedback. However, challenges such as technology gaps, privacy issues, and user readiness remain barriers that must be overcome. This study used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, and data for this study were collected from Google Scholar using predetermined keywords related to AI and higher education. The results of this study show that AI can enhance student learning through personalization, better access to learning materials, and real-time evaluation. Challenges such as technology gaps, privacy, and user readiness need to be addressed to maximize the benefits of AI in education. Further research and collaboration between educational institutions, technology developers, and governments are needed to overcome these barriers and capitalize on the existing opportunities